Formulation and Evaluation of Oral disintegrated tablets of Alfuzosin Hydrochloride using superdisintegrants - Leela Manasa K, Ramana G, Digpati Roy (Journal of Applied Pharmaceutical Science)
In the present work, orodispersible tablets of Alfuzosin Hcl were prepared by direct compression and sublimation methods with a view to enhance patient compliance. In these methods, varying concentrations of crospovidone, sodium starch glycolate and croscarmellose sodium of 3.3, 6.6 and 10% w/w were used, along with camphor used as subliming agent in sublimation method. The prepared batches of tablets were evaluated for hardness, friability, drug content, wetting time, dispersion time, disintegration time and dissolution studies. Based on disintegration time (approximately 13-18 seconds) all the promising formulations (from each method) were tested for in-vitro drug release pattern (in pH 6.8 phosphate buffer), drug-excipient interaction (FTIR spectroscopy) and short term stability studies. Among the promising formulations, the formulation F4 and F14 containing 10% w/w Crospovidone emerged as the overall best formulation (t50%1.79 and 1.21 minutes) based on drug release characteristic (in pH 6.8 phosphate buffer) compared to controlled formulation F1 (t50% >10 minutes).
Keywords: Orodispersible tablet, Alfuzosin, Crospovidone, Sodium starch glycolate, Croscarmellose sodium and Camphor.